1997
DOI: 10.1063/1.366194
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanisms of TiN oxidation beneath Pt thin films

Abstract: Oxidation kinetics are reported for TiN thin film diffusion barriers beneath polycrystalline Pt films of 50-200 nm thickness annealed in dry O 2 /N 2 ambients of varying oxygen partial pressure and total pressure near 1 atm. Oxygen resonance backscattering spectrometry was used to detect thin oxide layers at the Pt/TiN interface produced by oxidation annealing at 475-650°C. Over part of this temperature range, a linear oxidation rate law was observed for the buried TiN film, indicating the oxidation rate was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Our results for the Pt thin films with Ti adhesion layer are very consistent with results from literature [18,[36][37][38][39][40][41][42][43]. Both XRD and AES measurements showed evidence of oxidation of the Ti adhesion layer after annealing, which is enhanced in O 2 -rich environments, where in the AES depth profiles it was also observed that Ti had diffused through the Pt film to form an oxide either embedded in or on top of the Pt film.…”
Section: Platinum/titanium Thin Filmssupporting
confidence: 91%
“…Our results for the Pt thin films with Ti adhesion layer are very consistent with results from literature [18,[36][37][38][39][40][41][42][43]. Both XRD and AES measurements showed evidence of oxidation of the Ti adhesion layer after annealing, which is enhanced in O 2 -rich environments, where in the AES depth profiles it was also observed that Ti had diffused through the Pt film to form an oxide either embedded in or on top of the Pt film.…”
Section: Platinum/titanium Thin Filmssupporting
confidence: 91%
“…In the simple stacked-capacitor structure, the side of the barrier is directly exposed to the oxygen processing ambient, whereas in structures with a recessed barrier [5] or where the side of the barrier is covered with an insulating or noble-metal [6] layer, the barrier is primarily exposed to oxygen diffusing through the electrode grain boundaries [7]. In the simple stacked-capacitor structure, the side of the barrier is directly exposed to the oxygen processing ambient, whereas in structures with a recessed barrier [5] or where the side of the barrier is covered with an insulating or noble-metal [6] layer, the barrier is primarily exposed to oxygen diffusing through the electrode grain boundaries [7].…”
Section: Electrode and Barrier Propertiesmentioning
confidence: 99%
“…Since these high-permittivity ͑k͒ dielectrics are generally prepared in an oxidizing ambient at elevated process temperatures of above 450°C and require an additional improvement anneal after the high-k deposition and patterning process, [9][10][11][12][13][14] use of conventional sputtered TiN is no longer stable against oxidant diffusing through the Pt electrode. Since these high-permittivity ͑k͒ dielectrics are generally prepared in an oxidizing ambient at elevated process temperatures of above 450°C and require an additional improvement anneal after the high-k deposition and patterning process, [9][10][11][12][13][14] use of conventional sputtered TiN is no longer stable against oxidant diffusing through the Pt electrode.…”
Section: Introductionmentioning
confidence: 99%